DESAIN KENDALI KECEPATAN MOBILE ROBOT EMPAT RODA MEKANUM BERBASIS INVERSE KINEMATICS DAN PI ANTI WINDUP PADA KONTES ABU ROBOCON 2023 - Asyfia, Syifa Nurul; Abdul Aziz, Arif; Mulkan Rodiana, Irham (Telkatika: Jurnal Telekomunikasi Elektro Komputasi & Informatika, 2024)
ABU Robocon is a robotics competition in Asia – Pacific organized by the Asia-Pacific Broadcasting Union (ABU). In 2023, ABU Robocon is holding a contest with the theme "Casting Flower over Angkor Wat". The challenge of this year's competition is the obstacles on the playing field. It will be designed a mobile robot with a mechanical wheel-based to be able to pass through flat plane surfaces and inclined planes with an 18.43° slope on the playing field. PI Anti Windup control method is carried out, in controlling the speed of the robot. The results of the PI Anti-windup control show the system has an overshoot of 26% and a settling time that is in the range of 0.6 seconds to 1.7 seconds. The robot has a success rate of passing inclined plane obstacles of 75%. Keywords:ABU Robocon, mecanum wheel, PI Anti Windup